Efektifitas tea tree pada ibu hamil terhadap jerawat vulgaris di UPTD Puskesmas Sindang Kabupaten Indramayu - Oktaviani, Pearly Otis Putri (UKInstitute, 2024)
The prevalence of acne patients in Indonesia is approximately 80-85% among adolescents aged 15-18 years, 12% in women aged over 25 years, and 3% in the age group of 35-44 years. The purpose of this study is to determine the effectiveness of tea tree on pregnant women with vulgaris acne at the Sindang Community Health Center in Indramayu Regency. The population in this study includes all pregnant women with vulgaris acne at the Sindang Community Health Center in Indramayu Regency, totaling 30 individuals. Bivariate analysis in this study uses a paired sample t-test to observe differences before and after treatment. Based on the statistical test results using the Paired Samples Test, with the assistance of SPSS version 24 and a significance level of α = 0.05, the result is obtained with p = 0.000, which means p 0.05. Thus, H1 is accepted, indicating that tea tree is effective in treating vulgaris acne in pregnant women at the Sindang Community Health Center in Indramayu Regency. Furthermore, it is recommended to expand the research with a clinical trial design to gain a deeper understanding of the benefits and risks of using skincare products during pregnancy.